TRANSFORMASI SPIRITUAL WERKUDARA DALAM LAKON BIMA SUCI: ANALISIS MULTIDISIPLIN TERHADAP HEROIC JOURNEY DAN KONSTRUKSI MAKNA - Yunisa Wulandari; Suwardi Suwardi; Angga Bimo Satoto (Sabdasastra : Jurnal Pendidikan Bahasa Jawa, 2026)
Lakon Bima Suci represents one of the most complex and philosophical literary works within the Javanese wayang tradition. Despite extensive scholarly attention, in-depth research on the spiritual transformation of Werkudara using multidisciplinary approaches remains limited. The complexity of philosophical meanings and symbolism in this lakon requires comprehensive analysis to reveal its profound spiritual dimensions. This study aims to examine the spiritual transformation of Werkudara (Bima) in Lakon Bima Suci through a multidisciplinary approach that integrates perspectives from religious anthropology, analytical psychology, semiotics, and contemporary literary theory. The analytical focus centers on Werkudara's heroic journey in searching for Tirta Pawitra Kamandalu as a metaphor for spiritual journey toward self-realization. This research employs narratological analysis to dissect story structure, hermeneutic approaches for interpreting symbolic meanings, and phenomenological methods to reveal the spiritual experiences embodied in Werkudara's actions. The research findings demonstrate that Lakon Bima Suci not only presents an adventure story but also constitutes a sophisticated allegory of the individuation process and existential meaning-seeking. Werkudara's actions reflect archetypal patterns of heroic journey that are universal yet contextualized within the Javanese-Hindu worldview, depicting a journey from unconsciousness to spiritual enlightenment. Lakon Bima Suci represents a complex spiritual journey that successfully integrates universal heroic pattern elements with Javanese-Hindu philosophical values, offering profound perspectives on human spiritual transformation.